Is revenue sharing working for Major League baseball? A historical perspective - Elanjian, M. R.; Pachamanova, D. A. (The Sport Journal, 2009)
Abstract This article attempts to evaluate whether the system of revenue sharing in Major League Baseball since 2000 (after the Blue Ribbon Panel report) has had a statistically significant effect on team revenues, payroll, attendance, and performance. Analysis of data for two distinct time periods, 1995-2000 and 2001-2007, suggests that since the adoption of the current revenue sharing system (1) the ratio of the highest to lowest team revenue has decreased; (2) the marginal effect of revenue on performance as measured by percentage of wins during the regular season has improved in a way that has benefitted lower-revenue teams; (3) the payroll expenditures of the lowest revenue quartile teams have increased significantly; and (4) attendance levels for the lowest revenue quartile teams have increased slightly. Historical trend analysis suggests, however, that the system is working slowly.